2003
DOI: 10.1097/01.tp.0000069835.95442.9f
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mitochondrial Apoptotic Pathways in Human Renal Allografts After Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion injury in CAD kidney transplants is associated with a duration-dependent increase in tubular cell apoptosis, mediated at least in part by activation of mitochondrial pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(112 citation statements)
references
References 23 publications
5
102
0
5
Order By: Relevance
“…For example, it has been shown that ischemic injury to the kidney is associated with apoptosis (21,28 -30), upregulation of Fas (21,27,29), and enhanced ankyrin expression (22) in tubular epithelial cells, and Fasdeficient mice are protected from ischemic renal injury (27). In the study presented here, we have shown that in a model of early renal ischemia-reperfusion injury characterized by apoptotic tubule cell death, the expression of both ankyrin and Fas was markedly induced, and the interaction between these molecules remained intact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that ischemic injury to the kidney is associated with apoptosis (21,28 -30), upregulation of Fas (21,27,29), and enhanced ankyrin expression (22) in tubular epithelial cells, and Fasdeficient mice are protected from ischemic renal injury (27). In the study presented here, we have shown that in a model of early renal ischemia-reperfusion injury characterized by apoptotic tubule cell death, the expression of both ankyrin and Fas was markedly induced, and the interaction between these molecules remained intact.…”
Section: Discussionmentioning
confidence: 99%
“…We used well established murine models in which the structural and functional consequences of brief periods of renal ischemia have been previously documented (27)(28)(29)(30). Briefly, male Swiss-Webster mice (Taconic Farms, Germantown, NY) weighing 25 to 35 g were housed with a 12:12 h light:dark cycle and were allowed free access to food and water.…”
Section: Mouse Model Of Renal Ischemia-reperfusion Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Proximal and distal tubular cells were identified primarily by morphologic criteria, including the presence of a brush border, the cell size, and nuclearcytoplasmic ratio. Lectin histochemistry with Phaseolus vulgaris erythroagglutinin (Sigma, St. Louis, MO) and Arachis hypogaea (AH; Sigma) was used as a confirmatory assay to identify proximal and distal tubules, respectively, as described previously (26,27). Briefly, serial sections were deparaffinized, treated with 1.25% H 2 O 2 in methanol for 30 min, incubated with either Phaseolus vulgaris erythroagglutinin (1 g/ml) or AH (10 g/ml) for 60 min, and developed with diaminobenzidine.…”
Section: Apoptosis Assay In Kidney Biopsy Samplesmentioning
confidence: 99%
“…Following reperfusion, a complex series of events occur including generation of reactive oxygen and nitrogen species, generation of proinflammatory cytokines, alteration of microvascular activity, inflammation, and eventually tubular cell death (3). Morphological changes of kidney IR injury include effacement and loss of proximal tubule brush border, proximal tubular dilation and distal tubular casts, necrosis, and apoptosis of proximal tubular cells (6,17,39). In addition, rapid accumulation of massive neutrophils and monocyte/macrophages, and fewer leucocytes in the interstitium of injured kidney is another feature of renal IR injury (3,22,25).…”
mentioning
confidence: 99%